ORGANIZATION OF WORK WITH EDUCATIONAL TEXT IN THE PROCESS OF HUMANITARIAN TRAINING OF FUTURE PHILOLOGISTS ON THE BASIS OF COMPETENCE APPROACH (Pedagogy of Higher and Secondary Education, 2011)
The article explains the system will work with academic texts in the training of future humanitarian philologists on the basis of competence-based approach. Disclosed information aktivizatorskaya and motivational functions of academic teats; described forms of implementing the educational text.
Keywords: educational text; humanitarion training; competence approach; students philological discipline